Functional muscle power testing in young, middle-aged, and community-dwelling nonfrail and prefrail older adults - Zech, Astrid; Steib, Simon; Freiberger, Ellen; Pfeifer, Klaus (Archives of physical medicine and rehabilitation, 2011)
Zech A, Steib S, Freiberger E, Pfeifer K. Functional muscle power testing in young, middle-aged, and community-dwelling nonfrail and prefrail older adults. - Objective - To evaluate the stair climb (SC) and sit-to-stand (STS) transfer test for functional power assessment in young, middle-aged, and community-dwelling nonfrail and prefrail older adults. - Design - Cross-sectional study. - Setting - Sport science institute providing health-related exercise programs for older people. - Participants - Participants (N=60; age, 22-81y) were divided into groups of young (n=15; 20-30y), middle-aged (n=16; 40-60y), nonfrail older (n=16; >65y), and prefrail older adults (n=13; >65y). - Interventions - Not applicable. - Main Outcome Measures - SC and STS transfer power were measured on 2 separate occasions. - Results - Age and height correlated positively (P<.001) with both power measures. Multiple linear regression analysis showed that 67.9% (R2) of the variance in SC power and 31.3% (R2) of the variance in STS transfer power can be attributed to age and height. Significant age-related subgroup differences were found for SC power (P=.001). Nonfrail and prefrail older adults differed significantly in both power measures (P<.001). - Conclusions - The findings indicate that SC and STS transfer power are sensitive enough to distinguish between nonfrailty and prefrailty. This suggests that both tests are relevant clinical measures in older people.
Gesehen am 13.07.2022